IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DI SMP N 3 BANGLI KECAMATAN BANGLI, KABUPATEN BANGLI - Putu Elvira Pradnya Paramitha (JAPAM (Jurnal Pendidikan Agama), 2025)
The Independent Curriculum prioritizes the development of student character in alignmentwith the values of Pancasila. Currently, Pancasila values appear to be eroding in various aspects ofstudents' character. Indifference toward others, the environment, school regulations, and more,highlight the need for the implementation of the Pancasila Student Profile Strengthening Project (P5)in education. This initiative aims to cultivate dimensions such as faith and devotion to God Almighty,collaboration, critical thinking, and creativity. This study aims to: (1) describe the implementation ofthe Pancasila Student Profile Strengthening Project at SMP Negeri 3 Bangli; (2) examine the rolesof teachers, parents, and the community in the implementation of the project at SMP Negeri 3 Bangli;and (3) identify the implications of the project at SMP Negeri 3 Bangli. Theories used in this studyinclude behaviorist theory, motivation theory, and character theory. This research is a descriptivequalitative study using a phenomenological approach. Data were collected through observation,interviews, literature review, and documentation. The collected data were analyzed through datareduction, data presentation, and conclusion drawing/verification. The research findings include: (1)the implementation of the Pancasila Student Profile Strengthening Project at SMP Negeri 3 Bangli;(2) the roles of teachers, parents, and the community in supporting the project; and (3) theimplications of the project activities, which are: (a) enhancement of students’ faith, devotion to GodAlmighty, and noble character; (b) improvement in the dimension of collaboration among students;(c) development of students’ critical thinking skills; and (d) enhancement of students’ creativity.